ANALISA MODEL POHON DAN GRAF PADA GAME PERFECT WORLD 2 ONLINE - Nugraha, Wahyu; Syarif, Muhamad; Sabaruddin, Raja (STMIK KAPUTAMA, 2021)
The implementation of graphs and trees in the Perfect World Online Game is one example of the application of discrete mathematics in human activities, especially the world of entertainment. The internet is currently causing the development of online games to increase rapidly, as seen from the emergence of many online games with various genres such as Adventure, Action, Strategy, RPG, MMORPG and many more. MMORPG was chosen as the type of game to be discussed because in the game model and features many apply trees and graphs. With the help of graph and tree theory, we can further explore all the features that are fast in an online game.